Proceedings of the 32nd International ACM SIGIR Conference on Research and Development in Information Retrieval 2009
DOI: 10.1145/1571941.1572097
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the descriptiveness of web comments

Abstract: This paper investigates whether Web comments are of descriptive nature, that is, whether the combined text of a set of comments is similar in topic to the commented object. If so, comments may be used in place of the respective object in all kinds of cross-media retrieval tasks. Our experiments reveal that comments on textual objects are indeed descriptive: 10 comments suffice to expect a high similarity between the comments and the commented text; 100-500 comments suffice to replace the commented text in a ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
3

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 7 publications
1
16
0
3
Order By: Relevance
“…An important premise of our approach is that comments actually describe the commented item to some extent, which is what we have investigated earlier [5]. In short, we found that comments on text are indeed descriptive: 10 comments are sufficient to reach a considerable similarity between a text and its comments, which Copyright is held by the author/owner(s).…”
Section: Introductionmentioning
confidence: 65%
“…An important premise of our approach is that comments actually describe the commented item to some extent, which is what we have investigated earlier [5]. In short, we found that comments on text are indeed descriptive: 10 comments are sufficient to reach a considerable similarity between a text and its comments, which Copyright is held by the author/owner(s).…”
Section: Introductionmentioning
confidence: 65%
“…Al respecto, señala que diez comentarios son sufi cientes para determinar una gran similitud entre los textos y sus comentarios. De esta manera, los comentarios podrían ser utilizados en lugar del objeto que comentan en tareas de recuperación de textos (Potthast, 2009).…”
Section: Calidoscópiounclassified
“…Comments and messaging structure in blogs and shared social spaces have been used to understand dialogue based conversational behavior among individuals (Schuth et al, 2007) as well as in the context of summarization of social activity on the online platform (Lu et al, 2009;Hu et al, 2007) or to understand the descriptive nature of web comments (Potthast, 2009). Some prior work have also deployed conversational nature of comments to understand social network structure as well as in statistical analysis of networks (Gómez et al, 2008).…”
Section: Communication Modes In Social Network/social Mediamentioning
confidence: 99%